TEORI SOSIAL DALAM PERSPEKTIF TEORI KRITIS MAX HORKHEIMER - Sindung Tjahyadi (Jurnal Filsafat "WISDOM", 2007)
In this work, “Horkheimer’s critical theory” is critically discussed in its relation with the presence of “prestigious” fact achieved by positivistic sciences. However, positivistic sciences have many contributions in providing the new dimensions for human life. In the case of Horkheimer’s critical theory, it is clear that Horkheimer does not appreciate enough the positive-capitalistic approach. Even though, the antagonistic relation between “self” and “nature” in Horkheimer’s point of view must be investigated. For social scientists that has social theory orientations and rigorous and applicative methodology, Horkheimer’s critical theory is viewed as uncompleted social theory because he never provides a comprehensive method for social analyses. Even social theory properly leaves its function in “portraying” and analyzing community, Horkheimer reminds that there is a more important function of social theory called as “emancipatory-awareness”. If human beings do not believe in optimism to pick up the better situation or to realize their “utopia”, actually they have failed to sense their self-existence.